Hidup Sehat dalam Perspektif Islam: Integrasi Nilai Spiritual dalam Pendekatan Kesehatan Masyarakat - Abul A'la Al; Erlitha Azhari Dewi; Fabby Azhezinova; Muhammad Miftah Farid (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Health is a fundamental determinant of individual quality of life and productivity. In Islam, health is perceived as a holistic condition encompassing physical, mental, and spiritual dimensions. This study aims to examine the concept of a healthy lifestyle from an Islamic perspective and its relevance to modern public health approaches. The method employed is a literature review using normative-theological and conceptual approaches. The findings indicate that Islam establishes comprehensive principles of a healthy lifestyle, including the regulation of halal and thayyib dietary practices, balanced consumption, personal hygiene, physical activity, and spiritually grounded mental health. Evidence from the Qur’an and Hadith demonstrates that health is an integral part of maqashid al-sharia, particularly in the preservation of life (hifz al-nafs). This concept aligns with the promotive and preventive paradigms in modern public health. Therefore, the integration of Islamic values into health interventions has the potential to enhance the effectiveness of public health programs.